A framework of IoT-enabled vehicular noise intensity monitoring system for smart city - Rahim, Md. Abdur; Rahman, M.M.; Rahman, Md Arafatur; Abu Jafar, Md Muzahid; Syafiq Fauzi, Kamarulzaman (Springer, Cham, 2021)
The noise, sound pollution, and harshness are steadily increasing alarmingly from various vehicles such as lorries, vans, cars, and buses. It is considered a significant concern in our modern life due to the long-term harmful effect on human health. The excessive vehicular noise and sound pollution mainly affecting in specific areas of smart cities such as hospitals, educational institutes, various private/public organizations. As a result, people are suffering from neurocognitive problems. Therefore, controlling the sound pollution from vehicles are incredibly essential to mitigate health issues globally. However, minimal research was conducted by monitoring vehicular noise intensity in a smart city area using smart, reliable, and sophisticated technologies such as the internet of things (IoT) to mitigate these issues. This paper presents an enhanced intelligent IoT-enabled vehicular noise intensity monitoring system to protect the city dweller’s health-related difficulties by reducing sound pollution in the smart city. We are planned to propose an architectural framework using noise intensity measuring sensors, 360° Camera, 360° LIDAR, GPS (Global Positioning System) in the vehicle with IoT technology for monitoring individual vehicles and their nearby vehicles over the smart city. The proposed system can monitor real-timely vehicular noises and notify designated stakeholders (i.e., vehicle owner, city authority) promptly and stored in the cloud with valid proofs. The proposed system helps to develop an ideal vehicular noise monitoring system over the smart cities and the widespread significance of mitigating health problems that relate to sound pollution and increase public awareness.